Study of some virulence genes from uropathogenic Klebsiella pneumoniae and Pseudomonas aeruginosa isolated in Wasit Province, Iraq - Rana H. Raheema; Sabaa Hilal Hadi; Zainab Adil Ghani Chabuck (Medical Journal of Babylon)
Abstract Background: Klebsiella pneumoniae and Pseudomonas aeruginosa are the most common causes of nosocomial urinary tract infections (UTIs), and in recent years, these bacteria have become significantly more resistant to antibiotics. Objective: The objective of the study was to determine the frequency of uropathogenic K. pneumoniae and P. aeruginosa in clinical urine samples from patients with UTIs in Wasit Province. Materials and Methods: Initially, 100 clinical urine samples were taken for this investigation from (October 1 to December 1, 2022), and the isolates were initially identified using culture, microscopic analysis, and biochemical assays. Results: The findings of the biochemical results revealed that 16/100 isolates had a 16% positive response for K. pneumonia, and 13/100 isolates had a 13% positive response for P. aeruginosa. When DNA was recovered from the isolates, the nucleic acid purity was diverse from 1.8 to 2.0, and the concentration fluctuated from 50 to 360 mg/µL. By using molecular techniques, including the 16S rRNA gene, for confirmation of the diagnosis. These findings were validated by the polymerase chain reaction method used to detect the virulence genes fimH gene, where 4/16 (25%) and mrkA gene, where result 7/16 (43.75%) were positive in recovered K. pneumoniae isolated. And RNA polymerase subunit B (rpoB) gene where results 10/13 (76.92%) were positive in recovered P. aeruginosa isolated. Conclusion: In conclusion, the outcomes of this study presented a significant increase in biofilm-forming and multidrug-resistant K. pneumoniae isolates, which also harbor a wide range of virulence genes and used rpoB as high molecular identification properties to confirm the P. aeruginosa, the most efficient antibiotics for its treatment were Impinem and Nitrofurantoin for both K. pneumonia and P. aeruginosa.